Artificial placenta and womb technology: Past, current, and future challenges towards clinical translation. (19th September 2020) - De Bie, Felix R.; Davey, Marcus G.; Larson, Abby C.; Deprest, Jan; Flake, Alan W.
Abstract: Extreme prematurity remains a major cause of neonatal mortality and severe long‐term morbidity. Current neonatal care is associated with significant morbidity due to iatrogenic injury and developmental immaturity of extreme premature infants. A more physiologic approach, replacing placental function and providing a womb‐like environment, is the foundational principle of artificial placenta (AP) and womb (AW) technology. The concept has been studied during the past 60 years with limited success. However, recent technological advancements and a greater emphasis on mimicking utero‐placental physiology have improved the success of experimental models, bringing the technology closer to clinical translation. Here, we review the rationale for and history of AP and AW technology, discuss the challenges that needed to be overcome, and compare recent successful models. We conclude by outlining some remaining challenges to be addressed on the path towards clinical translation and opportunities for future research.